Glutathione peroxidase‐1 overexpression reduces oxidative stress, and improves pathology and proteome remodeling in the kidneys of old mice. Issue 6 (13th May 2020) - Chu, Yi; Lan, Renny S.; Huang, Rui; Feng, Hao; Kumar, Rahul; Dayal, Sanjana; Chan, Kung‐Sik; Dai, Dao‐Fu
Abstract: This study investigated the direct roles of hydrogen peroxide (H2 O2 ) in kidney aging using transgenic mice overexpressing glutathione peroxidase‐1 (GPX1 TG). We demonstrated that kidneys in old mice recapitulated kidneys in elderly humans and were characterized by glomerulosclerosis, tubular atrophy, interstitial fibrosis, and loss of cortical mass. Scavenging H2 O2 by GPX1 TG significantly reduced mitochondrial and total cellular reactive oxygen species (ROS) and mitigated oxidative damage, thus improving these pathologies. The potential mechanisms by which ROS are increased in the aged kidney include a decreased abundance of an anti‐aging hormone, Klotho, in kidney tissue, and decreased expression of nuclear respiratory factor 2 (Nrf2), a master regulator of the stress response. Decreased Klotho or Nrf2 was not improved in the kidneys of old GPX1 TG mice, even though mitochondrial morphology was better preserved. Using laser capture microdissection followed by label‐free shotgun proteomics analysis, we show that the glomerular proteome in old mice was characterized by decreased abundance of cytoskeletal proteins (critical for maintaining normal glomerular function) and heat shock proteins, leading to increased accumulation of apolipoprotein E and inflammatory molecules. Targeted proteomic analysis of kidney tubules from old mice showed decreased abundance of fatty acid oxidation enzymes and antioxidant proteins, as well as increased abundance of glycolytic enzymes and molecular chaperones. GPX1 TG partially attenuated the remodeling of glomerular and tubule proteomes in aged kidneys. In summary, mitochondria from GPX1 TG mice are protected and kidney aging is ameliorated via its antioxidant activities, independent and downstream of Nrf2 or Klotho signaling. Abstract : Glutathione Peroxidase‐1 overexpression reduces oxidative stress, preserves mitochondrial cristae structures, and improves kidney pathology and proteome gemodeling in the glomeruli and tubules of old mouse kidneys. These beneficial effects are downstream and independent of Klotho and Nrf2 signaling.